Olhares cruzados: a figuração da personagem feminina em Manoel de Oliveira e Agustina Bessa-Luís - Cristiane Costa Baiotto (2017)
The purpose of this paper is to analyze the figuration of woman characters in Manoel de Oliveiras movies adapted from the fiction of Agustina Bessa-Luís. The movies are: Francisca (1981), Vale Abraão (1993), O Convento (1995), Party (1996), Inquietude (1998), O Princípio da Incerteza (2002) and Espelho Mágico (2005). We approached three guiding themes that can be found in Bessa-Luís Dicionário Imperfeito (1997): Woman (volition); Woman (love) e Woman (solitude). These three guiding themes function as theoretical operators capable of providing a broad critical perspective on the construction of the characters, both in the literary text and in the filmic text, central element for the analysis developed here.